Catalogue of the type specimens in the fish collection of the Kunming Natural History Museum of Zoology, Kunming Institute of Zoology, Chinese Academy of Sciences - Min, Rui; Yang, Junxing; Chen, Xiaoyong (Zootaxa, 2026)
A comprehensive checklist of type specimens preserved in the fish collection of the Kunming Natural History Museum of Zoology, Kunming Institute of Zoology, Chinese Academy of Sciences, is presented. The collection dates back to the late 1950s. As of early 2025, this repository comprises approximately 200,000 specimens, including 2660 type specimens spanning 6 orders, 21 families, 86 genera, and 245 species. The type-specimens collection is notably rich in Cypriniformes, with 198 species from 12 families and 65 genera, and Siluriformes, with 38 species from 4 families and 12 genera. Additionally, it includes 1 species each of Anabantiformes and Beloniformes, 5 species of Gobiiformes from a single genus, and 2 species of Synbranchiformes from a solitary genus. All original description references of the 245 species and their current valid taxonomy have been verified. Geographically, the specimens are predominantly sourced from China and neighboring countries, particularly the southwestern region of China.